Coming Home? The Integration of Hmong Refugees from Wat Tham Krabok, Thailand, into American Society - Grit Grigoleit (Hmong Studies Journal, 2007)
In December 2003, the U.S. State Department officially announced the acceptance of roughly 15,000 Hmong refugees from Wat Tham Krabok, Thailand, into the United States of America. The Hmong refugees were scheduled to be resettled for family reunification in established Hmong communities. As social science research on migration indicates, the existence of ethnic communities is crucial for a successful adaptation to a host society for newcomers. Ethnic communities thereby serve as a buffer zone and provide initial assistance, which is especially important when governmental integration measures are not sufficient. In the case of the Hmong refugee resettlement, the U.S. economic and social incorporation efforts were inefficient, due to cutbacks in U.S. Federal funding and welfare reforms, causing a greater reliance on the receiving Hmong communities. This raises a number of questions about how much an ethnic community can absorb and is able to bear in order to fulfill the newcomers’ needs. What are the limits and how does this affect the initial integration of the newcomers?